Integration of Circular Economy and Local Biopharmaca in the Production of Chemical Residue-Free Healthy Chicken Eggs in Panti Subdistrict, Jember - Lelono, Asmoro; Akhmad Rikhwan; Rizky Surya Wijaya; Adelia Nur Fahmi; Nurul Fajril Azizah; Farahdillah Rafiatul Nurhasanah; Arumiannisa Altamaputri (Faculty of Mathematics and Natural Sciences, University of Jember, 2026)
Native chicken farming in Suci Village, Jember, faces significant challenges, including high mortality rates due to extreme weather and a heavy reliance on chemical antibiotics, which triggers the risk of Antimicrobial Resistance. This community service program aims to implement the downstreaming of superior native chicken strains developed by the Avian Immunity research team through a